2015
DOI: 10.1002/ejp.814
|View full text |Cite
|
Sign up to set email alerts
|

Altered nociception and morphine tolerance in neuropeptide FF receptor type 2 over‐expressing mice

Abstract: Our results suggest that neuropeptide FF R2 is mainly involved in the modulation of nociception and tolerance to morphine antinociception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…When facing stressful condition NPFF may signal through NPFFR2 signalling to modulate anxiety‐like behaviors. This would be in line with studies showing the resistance of Npffr2 −/− mice to the single prolong stress (a stress model of post‐traumatic stress disorder)—induced increase in anxiety‐like behaviors, 21 and studies showing anxiogenic phenotypes from enhanced NPFFR2 activation either through receptor overexpression or chronic agonist treatment 23,55 …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…When facing stressful condition NPFF may signal through NPFFR2 signalling to modulate anxiety‐like behaviors. This would be in line with studies showing the resistance of Npffr2 −/− mice to the single prolong stress (a stress model of post‐traumatic stress disorder)—induced increase in anxiety‐like behaviors, 21 and studies showing anxiogenic phenotypes from enhanced NPFFR2 activation either through receptor overexpression or chronic agonist treatment 23,55 …”
Section: Discussionsupporting
confidence: 72%
“…This would be in line with studies showing the resistance of Npffr2 −/− mice to the single prolong stress (a stress model of post-traumatic stress disorder)induced increase in anxiety-like behaviors, 21 and studies showing anxiogenic phenotypes from enhanced NPFFR2 activation either through receptor overexpression or chronic agonist treatment. 23,55 The high concentration of NPFF expression in the brainstem, where many other neurons are being targeted by factors that control feeding behavior and energy homeostasis control, makes NPFF also a likely player in this regulatory loop. Pharmacological studies demonstrated that NPFF family peptides administered i.c.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-peptide NPFFR2 agonists, AC-263093 (2-[(3,4-dibromophenyl) methylene]-hydrazine-carboximidamide hydrochloride) and CFMHC (2-[[4-chloro-3-(trifluoromethyl)phenyl]methylene]-Hydrazinecarboximidamidehydrochloride) were used in current study [ 26 ]. The preparation of AC-263093 and CFMHC was described previously [ 25 , 49 ]. The drugs were dissolved in a vehicle solution consisting of DMSO: Tween 20: saline at a 1:2:17 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…The main behavioural symptom of naloxone-precipitated withdrawal response, jumping, was evaluated according to previous studies (Lin, Kao, Day, Chang, & Chen, 2016). Briefly, mice were injected with increasing doses of drug at an injection interval of approximately 8 hr.…”
Section: Naloxone-precipitated Withdrawal Testmentioning
confidence: 99%